Integrated evaluation of a panel of neurochemical biomarkers to optimize diagnosis and prognosis in amyotrophic lateral sclerosis. (23rd March 2022) - Falzone, Yuri Matteo; Domi, Teuta; Mandelli, Alessandra; Pozzi, Laura; Schito, Paride; Russo, Tommaso; Barbieri, Alessandra; Fazio, Raffaella; Volontè, Maria Antonietta; Magnani, Giuseppe; Del Carro, Ubaldo; Carrera, Paola; et al.
Abstract: Background and purpose: This study was undertaken to determine the diagnostic and prognostic value of a panel of serum biomarkers and to correlate their concentrations with several clinical parameters in a large cohort of patients with amyotrophic lateral sclerosis (ALS). Methods: One hundred forty‐three consecutive patients with ALS and a control cohort consisting of 70 patients with other neurodegenerative disorders (DEG), 70 patients with ALS mimic disorders (ALSmd), and 45 healthy controls (HC) were included. Serum neurofilament light chain (NfL), ubiquitin carboxyl‐terminal hydrolase isozyme L1 (UCHL1), glial fibrillary acidic protein (GFAP), and total tau protein levels were measured using ultrasensitive single molecule array. Results: NfL correlated with disease progression rate ( p  < 0.001) and with the measures of upper motor neuron burden ( p  < 0.001). NfL was higher in the ALS patients with classic and pyramidal phenotype. GFAP was raised in ALS with cognitive–behavioral impairment compared with ALS with normal cognition. NfL displayed the best diagnostic performance in discriminating ALS from HC (area under the curve [AUC] = 0.990), DEG (AUC = 0.946), and ALSmd (AUC = 0.850). UCHL1 performed well in distinguishing ALS from HC (AUC = 0.761), whereas it was not helpful in differentiating ALS from DEG and ALSmd. In multivariate analysis, NfL ( p  < 0.001) and UCHL1 ( p  = 0.038) were independent prognostic factors. Survival analysis combining NfL and UCHL1 effectively stratified patients with lower NfL levels ( p  < 0.001). Conclusions: NfL is a useful biomarker for the diagnosis of ALS and the strongest predictor of survival. UCHL1 is an independent prognostic factor helpful in stratifying survival in patients with low NfL levels, likely to have slowly progressive disease. GFAP reflects extramotor involvement, namely cognitive impairment or frontotemporal dementia. Abstract : Neurofilament light chain (NfL) is a useful biomarker for the diagnosis of amyotrophic lateral sclerosis and the strongest predictor of survival. Ubiquitin carboxyl‐terminal hydrolase isozyme L1 is an independent prognostic factor and may be helpful in further stratifying the prognosis of patients showing low NfL concentrations. Glial fibrillary acidic protein reflects extramotor involvement, namely, cognitive impairment or frontotemporal dementia.